2012
DOI: 10.3109/09638288.2011.645115
|View full text |Cite
|
Sign up to set email alerts
|

Coping with multiple sclerosis as a couple: ‘peaks and troughs’ – an interpretative phenomenological exploration

Abstract: These results will assist clinicians better comprehend how those with MS and their spouses cope in an interconnected way and this in turn affects their experience of rehabilitation. Results from this research indicated that clinicians need to be sensitive to the individual coping strategies of both members of a couple where one has MS, and address the changing needs of their relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 54 publications
4
94
1
1
Order By: Relevance
“…The family unit was often the first to know about the diagnosis (Irvine et al, 2009;Stuart and Sullivan, 1982) and the first to provide social support. In the three studies examining couples, the spouse was described as the main source of support (Boland et al, 2012;Johnson et al, 2010;Douglas et al, 2008). This relationship appeared to be reciprocal (Boland et al, 2012), so that both the person with MS and their partner received support whilst they came to terms with the diagnosis, representing the shared difficulties associated with MS. Mutual support was a common theme identified in three studies (Boland et al, 2012;Johnson et al, 2010;Liedstrom et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The family unit was often the first to know about the diagnosis (Irvine et al, 2009;Stuart and Sullivan, 1982) and the first to provide social support. In the three studies examining couples, the spouse was described as the main source of support (Boland et al, 2012;Johnson et al, 2010;Douglas et al, 2008). This relationship appeared to be reciprocal (Boland et al, 2012), so that both the person with MS and their partner received support whilst they came to terms with the diagnosis, representing the shared difficulties associated with MS. Mutual support was a common theme identified in three studies (Boland et al, 2012;Johnson et al, 2010;Liedstrom et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the three studies examining couples, the spouse was described as the main source of support (Boland et al, 2012;Johnson et al, 2010;Douglas et al, 2008). This relationship appeared to be reciprocal (Boland et al, 2012), so that both the person with MS and their partner received support whilst they came to terms with the diagnosis, representing the shared difficulties associated with MS. Mutual support was a common theme identified in three studies (Boland et al, 2012;Johnson et al, 2010;Liedstrom et al, 2010). In studies where the person with MS was single or divorced, other family members, such as parents or children, appeared to be the main source of social support (Boland et al, 2012;Liedstrom et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly we note that as carers' conflicting interpersonal demands change over time 4,29 this is reflected in their engagement with peer accounts. In particular, we observed that, following diagnosis, MS carers primarily engaged with those forms of peer account offering information about the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we would expect to see carers engaging in a similar process of information self-regulation as has been observed for patients 11 . The changing nature of the disease has important implications for the ways in which both MS patients and their carers cope with daily stressors 29 , which in turn may impact upon their desire for engagement with online health information 11 . Carers themselves may experience a shifting sense of identity from an initial reluctance to accept the role of carer 30 to recognition that much later on they are also in need of care 31 .…”
Section: Introductionmentioning
confidence: 99%